Evaluasi Manajemen Pembelajaran Pada Siswa Tunaganda di SD Negeri Bangunrejo 2 Yogyakarta (Sekolah Tinggi Ilmu Tarbiyah (STIT) Lingga, 2023)
This research aims to evaluate the implementation of learning management for students with multiple needs so that it can be seen what aspects have gone well, not optimal and which do not need to be implemented. This research using descriptive qualitative method was conducted at elementary school Bangunrejo 2 Yogyakarta in grades 1st and 5th. The data collected by observations, interviews and documents from trusted sources. From the results of the research it was found that the learning plan used special learning planning (PPI), the learning implementation had general and special explanations, the strategy for implementing the learning of multiple need students was separated from their friends, the sitting position was at the front, the talking distance was no more than 2 meters, suitability between mouth movements and the intent to be conveyed and pat him on the shoulder first before asking him to speak. While on the results of the assessment students get scores below standard. Keyword: Evaluation, learning management, multiple needs